Halal Cosmetic Knowledge and Purchasing Decisions Among Indonesian Muslim Students - Syaripudin, Eneng Chynta Zahra; Hakim, Abdul; Atmaja, Ria Ramadhani Dwi (Halal Science, 2026)
The expanding global cosmetics market underscores the need to examine factors guiding young consumers, yet a distinct gap remains in understanding how operational halal literacy shapes purchasing paths among future pharmacy professionals. This study evaluates the statistical association between halal cosmetic knowledge and purchasing decisions among students at UIN Malang. Utilizing a quantitative design, survey data were collected via purposive non-probability sampling from 105 respondents, following preliminary instrumentation testing (n=35). Data were evaluated using descriptive metrics and simple linear regression analysis. Descriptive findings indicated that 72.38% of respondents possessed high knowledge of halal cosmetics, and 84.76% demonstrated high purchasing decision levels. Simple linear regression analysis revealed a positive, statistically significant directional association between halal cosmetic knowledge and purchasing choices (β = 0.502; p = 0.001). The model fit demonstrated an F-statistic of 34.697 (p = 0.001) with a coefficient of determination (R2 = 0.252), proving that knowledge accounts for 25.2% of the variance in students' purchasing decisions. While the non-probability sampling design and cross-sectional nature of this study limit broader geographic generalizability and preclude assumptions of strict longitudinal causality, the findings confirm that advanced cognitive literacy is a vital indicator in guiding compliant product selection. In conclusion, halal cosmetic knowledge significantly and positively positions consumer choice, operating within a wider multi-factor market ecosystem. These insights provide baseline evidence for regulatory authorities and industries to expand targeted educational frameworks that foster transparent, halal-conscious consumer behavior among highly educated populations.